Strategi Pemasaran Konveksi Simple Cloth Industri Dalam Menarik Minat Konsumen Melalui Media Instagram - Rizqi Amanda Rachmah; Didi Permadi; Sarwo Edy (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The increasing competition in the marketing world in various aspects, makes the convection industry must be smart in attracting consumers. The convection industry is required not only to rely on product quality alone, but also requires an effective marketing strategy to build public trust and loyalty. This study focuses on the digital marketing communication strategy of Simple Cloth Industry. The problem that arises in this study is the need for uniforms, sashes, work shirts and other convections that require a trusted convection. Simple Cloth Industry has a great opportunity to market its convection business by providing direct offers and making Instagram the best portfolio in its business. This research method uses qualitative descriptive with the marketing mix theory from Kotler & Keller. Data collection techniques are obtained from the results of observations and interviews with Simple Cloth Industry. This study shows that Simple Cloth Industry has used Instagram in accordance with the theory of Kotler & Keller regarding the marketing mix, namely product optimization, price, location and promotion. Thus Simple Cloth Industry can develop until now because of the digital promotion that continues to grow. This study also found that Simple Cloth Industry has succeeded in creating strong relationships with customers through the use of structured and consistent social media so that relationships are well established.